2004
DOI: 10.1682/jrrd.2003.03.0038
|View full text |Cite
|
Sign up to set email alerts
|

Mobility function in older veterans improves after blind rehabilitation

Abstract: This study was conducted to investigate the effects of blind rehabilitation training on self-reported mobility function in visually impaired adults. Mobility function was assessed with a questionnaire administered before and 2 months after subjects completed a comprehensive blind rehabilitation program that included orientation and mobility training. Subjects rated the level of difficulty performing in 26 of 34 mobility situations as significantly lower after rehabilitation. Subjects also rated their confidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 9 publications
0
22
0
Order By: Relevance
“…In this regard, the development of a standardized instrument similar to the OSIVQ that can be used by the blind and visually impaired could be of crucial importance. Moreover, it seems relevant to explore whether rehabilitative approaches for blind people should be tailored to these individual preferences and skills in order to implement more effective strategies for dealing with the environment (Kuyk et al, 2004). For instance, rehabilitation programs including orientation and mobility training and favoring coding of the environment based on its spatial features instead of verbal descriptions might foster more efficient spatial representations in those with inherent preferences for spatial imagery, whereas individuals more inclined to object imagery or verbal coding strategies might benefit from alternative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the development of a standardized instrument similar to the OSIVQ that can be used by the blind and visually impaired could be of crucial importance. Moreover, it seems relevant to explore whether rehabilitative approaches for blind people should be tailored to these individual preferences and skills in order to implement more effective strategies for dealing with the environment (Kuyk et al, 2004). For instance, rehabilitation programs including orientation and mobility training and favoring coding of the environment based on its spatial features instead of verbal descriptions might foster more efficient spatial representations in those with inherent preferences for spatial imagery, whereas individuals more inclined to object imagery or verbal coding strategies might benefit from alternative approaches.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Engel et al and Kuyk et al demonstrated significant improvements in mobility-related ADLs after specific orientation and mobility training programmes, although it was not possible to calculate effect sizes from the data presented. 52,87 Horowitz et al reported small to medium effect sizes for functional outcomes in a large group of participants (N=395) after completion of a group based 'Adaptive Skills Training Programme'. 73 Farish and Wen found large effect sizes, particularly for near work, daily living skills and communication skills, in their evaluation of outcomes of 57 older people undergoing another new service, the "Independent Living Services Programme" for older persons in Mississippi.…”
Section: Effect Of Rehabilitation On Visual Function and Activitiementioning
confidence: 99%
“…141 Despite the conflicting evidence, overall it seems that the larger effects reported in the literature tend to come from intensive rehabilitation programmes e.g. 87,143 , although other studies have shown that it is possible to obtain a medium or large effect size with a relatively low dose intervention. 61,144 …”
Section: Figure 3 About Herementioning
confidence: 99%
“…There is no standardized assessment of low vision O&M 3 , but the O&M research literature is dominated by a few approaches, with a combination of variants of walking speed and obstacle avoidance contacts being the most common 4,5 . It is also a common approach to seed the environment with obstacles, increasing the opportunities for detection/avoidance/contact 6,7,8 .…”
Section: Methodsmentioning
confidence: 99%